Outcomes after Ross procedure in adult patients: A meta‐analysis and microsimulation. Issue 5 (13th March 2019) - Sibilio, Serena; Koziarz, Alex; Belley‐Côté, Emilie P.; McClure, Graham R.; MacIsaac, Sarah; Reza, Seleman J.; Um, Kevin J.; Lengyel, Alexandra; Mendoza, Pablo; Alsagheir, Ali; Alraddadi, Hatim; Gupta, Saurabh; et al.
Abstract: Objective: We conducted a meta‐analysis to estimate the risk of adverse events, life expectancy, and event‐free life expectancy after the Ross procedure in adults. Methods: We searched databases for reports evaluating the Ross procedure in patients aged more than or equal to 16 years of age. A microsimulation model was used to evaluate age‐ and gender‐specific life expectancy for patients undergoing the Ross procedure. Results: Data were pooled from 63 articles totaling 19 155 patients from 20 countries. Perioperative mortality was 2.5% (95% confidence interval [CI]: 1.9‐3.1; N  = 9978). We found a mortality risk of 5.9% (95% CI: 4.8‐7.2) at a mean follow‐up of 7.2 years ( N  = 7573). The rate of perioperative clinically significant bleeding was 1.0% (95% CI: 0.1‐3.0); re‐exploration for bleeding 4.6% (95% CI: 3.1‐6.3); postoperative clinically significant bleeding from 30 days until a mean of 7.1 years was 0.5% (95% CI: 0.2‐1.0). At a mean of 6.9 years of follow‐up, reintervention rate of any operated valve was 7.9% (95% CI: 5.7‐10.3). The risk of valve thrombosis was 0.3% (95% CI: 0.2‐0.5) at 7.6 years; peripheral embolism 0.3% (95% CI: 0.2‐0.4) at 6.4 years; stroke 0.9% (95% CI: 0.7‐1.2) at 6.5 years; and endocarditis 2.1% (95% CI: 1.6‐2.6) at 8.0 years. Microsimulation reported a 40‐year‐old undergoing the Ross procedure to have a life expectancy of 35.4 years and event‐free life expectancy of 26.6 years. Conclusions: Ross procedure in nonelderly adults is associated with low mortality and low risk of adverse events both at short‐ and long‐term follow‐up. The surgical community must prioritize a large, expertize‐based randomized controlled trial to definitively address the risks and benefits of the Ross procedure compared to conventional aortic valve replacement.